2021
DOI: 10.1101/2021.03.08.434514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Legionella pneumophila CRISPR-Cas suggests recurrent encounters with Gokushovirinae

Abstract: Legionella pneumophila is a ubiquitous freshwater pathogen and the causative agent of Legionnaires’ disease. This pathogen and its ability to cause disease is closely tied to its environmental encounters. From phagocytic protists, L. pneumophila has 'learned' how to avoid predation and exploit conserved eukaryotic processes to establish an intracellular replicative niche. Legionnaires' disease is a product of these evolutionary pressures as L. pneumophila uses the same molecular mechanisms to replicate in graz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…However, Lammertyn et al [ 46 ] were the first to report on the isolation and preliminary characterisation of bacteriophages active against L. pneumophila , subsequently highlighting the potential of bacteriophage biocontrol of this environmental pathogen. While no additional studies have reported on the isolation of L. pneumophila bacteriophages, using genomic analyses of 600 L. pneumophila isolates, Deecker et al [ 47 ] recently reported that the L. pneumophila isolates analysed in their study were devoid of prophages, and that bacteriophages targeting L. pneumophila are most likely lytic gokushoviruses ( Microviridae family), which are found in various aquatic environments.…”
Section: Opportunities For Bacteriophage Biocontrol In the Consumer W...mentioning
confidence: 99%
“…However, Lammertyn et al [ 46 ] were the first to report on the isolation and preliminary characterisation of bacteriophages active against L. pneumophila , subsequently highlighting the potential of bacteriophage biocontrol of this environmental pathogen. While no additional studies have reported on the isolation of L. pneumophila bacteriophages, using genomic analyses of 600 L. pneumophila isolates, Deecker et al [ 47 ] recently reported that the L. pneumophila isolates analysed in their study were devoid of prophages, and that bacteriophages targeting L. pneumophila are most likely lytic gokushoviruses ( Microviridae family), which are found in various aquatic environments.…”
Section: Opportunities For Bacteriophage Biocontrol In the Consumer W...mentioning
confidence: 99%